Nasir Khusraw’s Hermeneutic Philosophical Theology - Mohammadamin Shahjouei; Parviz Morewedge (حکمت اسرا)
متن ارائه شده، ترجمه مقاله زیر از آقای دکتر پرویز مروّج است که ذیلا چاپ شده استKnowledge and Liberation: A Treatise on Philosophical Theology, by Nasir Khusraw, a new edition and English translation of the Gushayish wa Rahayish by Faquir M. Hunzai, with an introduction by Parviz Morewedge entitled Nasir Khusraw’s Hermeneutic Philosophical Theology and his commentary, London: I. B. Tauris in association with the Institute of Ismaili Studies, 1998, xii+132+92 (in Persian) pp.